Neural correlates of the contextual interference effect in motor learning: a transcranial magnetic stimulation investigation - Lin, C.-H.; Winstein, C. J.; Fisher, B. E.; Wu, A. D. (Journal of Motor Behavior, 2010)
The authors applied transcranial magnetic stimulation (TMS) to investigate the causal role of the primary motor cortex (M1) for the contextual-interference effect in motor learning. Previous work using a nonfocal TMS coil suggested a casual role for M1 during high-interference practice conditions, but this hypothesis has not yet been proven. In the 1st experiment, participants practiced 3 rapid elbow flexion-extension tasks in either a blocked or random order, with learning assessed by a delayed retention test. TMS was delivered immediately after feedback during practice using a circular coil, centered over the contralateral M1. Each participant practiced with 1 of 3 TMS conditions: no TMS, real TMS, or sham TMS. Although no significant differences were observed between groups during acquisition, retention of the random group was better than the blocked group. The learning benefits of random practice were attenuated in the real-TMS condition, but not in the sham-TMS or no-TMS conditions. In the 2nd experiment, the authors studied the effects of suprathreshold TMS and subthreshold TMS over M1, lateral premotor cortex, and peripheral arm stimulation using a focal figure-8 coil on motor learning under random practice conditions. The authors found that only suprathreshold TMS on M1 produced significant disruption of retention compared to the other stimulation conditions. Results suggest that a high-threshold neuronal population within M1 is causally important for enhanced retention following random, but not block, practice. Results also support the early intertrial interval as a critical period of M1 activity during practice. Overall, these results suggest neural circuits within M1 contribute to motor learning processing that depends on learners' training experience. Results contribute to knowledge of the critical and specific role that M1 plays in generating a learning advantage following high-interference practice conditions.